1978
DOI: 10.3758/bf03197477
|View full text |Cite
|
Sign up to set email alerts
|

Holistic vs. attribute repetition effects in classifying stimuli

Abstract: The effect of the just previous stimulus on the current response was determined in three speeded classification experiments. When the stimuli were perceptual patterns, and when they were words, there was marked facilitation if the previous stimulus was identical to the current stimulus. When successive perceptual stimuli were composed of identical elements, but in a changed configuration, there was no measureable sequential effect on "same" response times. These results are for integral stimuli. When stimuli a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…The highest pitched stimuli in Experiment 3A, for instance, will follow each possible pitch transition (from 0 to 11 steps) equally often, whereas stimuli with more medial values of pitch will only have smaller pitch transitions (e.g., from oto 6 steps). We also know that RTs are longer to larger stimulus transitions than to smaller transitions (King, Gruenewald, & Lockhead, 1978). Therefore, even though RTs as a function of sequence were similar for both outlier and cluster stimuli (as demonstrated in Experiment 3B), the RTs averaged across all trials should be longer for the outlier stimuli than for the central stimuli, because there are many more instances oflarge differences between successive stimuli when outliers are judged than when central stimuli are judged.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The highest pitched stimuli in Experiment 3A, for instance, will follow each possible pitch transition (from 0 to 11 steps) equally often, whereas stimuli with more medial values of pitch will only have smaller pitch transitions (e.g., from oto 6 steps). We also know that RTs are longer to larger stimulus transitions than to smaller transitions (King, Gruenewald, & Lockhead, 1978). Therefore, even though RTs as a function of sequence were similar for both outlier and cluster stimuli (as demonstrated in Experiment 3B), the RTs averaged across all trials should be longer for the outlier stimuli than for the central stimuli, because there are many more instances oflarge differences between successive stimuli when outliers are judged than when central stimuli are judged.…”
Section: Discussionmentioning
confidence: 96%
“…Fletcher (1981) concluded that the presence or absence of repetition effects depends on practice: Early in practice, subjects displaya strong stimulus repetition effect, which progresses into a response repetition effect later in practice (see also Bertelson, 1965;Rabbitt, 1968). Pashler and Baylis (1991) report that response-repetition effects, as separate from stimulus-repetition effects, occur only when the category members differ on some superficial attribute (e.g., color, in a letter classification task; see also Lockhead, Gruenewald, & King, 1978). Several things need to be untangled for us to understand what occurs when people judge stimulus attributes; some of them are examined here.…”
Section: Sequence Effectsmentioning
confidence: 99%
“…In addition, the present study asked whether the effects of visual dimension changes and of response changes would interact at some point in the processing, which may be expected from the behavioral literature (e.g., Hommel, 1998;Kingstone, 1992;Lockhead et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the statistical interaction between the first-order defining-feature repetition effect and the first-order reported-feature repetition effect could be seen to challenge the independence of the two effects. However, when participants are asked to respond to a single dimension of multidimensional stimuli, it is common to find that repetition ofthe reported dimension interacts with repetition of the irrelevant dimension (Fletcher, 1981;Hommel, 1998;Lockhead, Gruenewald, & King, 1978). Such an interaction typically takes the following form.…”
Section: Mmentioning
confidence: 99%